Identification and Assessment of Plasmodium berghei Merozoites and Cell Cycle by Flow Cytometry. (25th January 2021) - Li, Qigui; Xie, Lisa H; Zhang, Jing; Pybus, Brandon S
ABSTRACT: Background: The asexual blood stages of the Plasmodium berghei life cycle including merozoites are attractive targets for transmission blocking vaccines and drugs. Improved understanding of P. berghei life cycle stage growth and development would provide new opportunities to evaluate antimalarial vaccines and drugs. Methods: Blood stage samples from C57BL/6 albino mice infected with P. berghei sporozoites were singly stained with a high binding affinity deoxyribonucleic acid dye, YOYO-1, and measured by flow cytometry (FCM). Duplicate slides were made from samples and stained with diluted Giemsa's and YOYO-1, respectively. Correlated results were compared by FCM, light microscopy, and fluorescent microscopy. Results: Complete life cycle stage determination and analysis by FCM is reported to include merozoites, ring forms, trophozoites, immature, and mature schizonts. FCM demonstrated a clear separation between each stage using their unique fluorescence distribution. When compared to light microscopy, a strong correlation ( r   2  = 0.925 to 0.974) was observed in determining the ring forms, trophozoites, and schizonts phases, but only a moderate correlation ( r   2  = 0.684 to 0.778) was observed for merozoites. The identification and measurement of merozoites suggest that FCM is a useful technique to monitor the entire life stage of the parasite. Initial stage-specific data demonstrated that mefloquine has a mode of action on mature parasite forms, and artesunic acid was rapidly effective against merozoites and other immature and mature parasite forms with higher killing. Conclusion: Blood stage parasites in each individual life stage, including merozoites, are reliably identified and quantified quickly by FCM, making this technique an ideal alternative to microscopy. This integrated whole life stage model, particularly with confirmed determination of merozoite population, could widely be used for drug and vaccine research in malaria therapy and prophylaxis.